EFEKTIVITAS KOMUNIKASI ADVERTORIAL PEMERINTAH KABUPATEN KAMPAR PADA KORAN RIAU POS DI KHALAYAK PEMBACA KECAMATAN BANGKINANG - Fallantra, Renny Ilda; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Effectiveness is a state that shows the success or failure of management activities in achieving goals. While communication is a process of delivering messages by the communicator to the communicant through the media that causes certain consequences. There are many types of messages or information delivered by an organization to the public, so the delivery requires adequate channels, both in terms of time, target public and its activities. One of the media commonly used by organizations to communicate to the public is through mass media, namely newspapers through the advetorial column. Likewise, the Kampar District Government used the Riau Pos newspaper as a medium of communication with the community. In line with the function of the mass media, one of which runs social control in the community. The purpose of this research is to find out how much the effectiveness of the advertorial government of Kampar Regency in the Riau Pos Newspaper in the audience of Bangkinang Kota. This research used quantitative research methods, with data collection techniques, namely through the distribution of questionnaire sheets to readers or customers of Riau Pos Newspapers with a sample size of 96 which is determined through random sampling techniques. Data analysis techniques in this research used descriptive statistical techniques.The results of this research indicate that the level of Advertorial Effectiveness of Kampar District Government in the Newspaper of Riau Post in the reader audience Kecamatan Bangkinang Kota is classified as effective. This can be seen from the results of data processing based on six indicators, each indicator reaching a scale of 3.13 on the receiver indicator, a scale of 2.94 on the message content indicator, a scale of 3.25 on the channel indicator ( media), a scale of 2.99 in the format indicator, a scale of 2.96 in the indicator of the source of the message (source), and a scale of 2.97 in the indicator of timeliness. So that the conclusion obtained by using the average formula of all indicators is 2.54 which is included in the effective range. This shows that the Government of Kampar Regency Advertorial in Riau Pos Newspaper is an effective medium for the Government's communication facilities to the public.  Keyword: Effectiveness communication, Advertorial, and Riau